Chlorogenic Acid Functionalized Tin Oxide-Sodium Alginate Hybrid Nanomaterials Induce Oxidative Stress-Mediated Apoptosis in Breast Cancer MDA-MB-231 Cells - Baby, Shakila; Alyami, Nouf M.; Aljawdah, Hossam M.; Alharbi, Sulaiman Ali; Arulselvan, Palanisamy; Jaganathan, Saravana Kumar; Hussein-Al-Ali, Samer Hasan; Muruganantham, Bharathi (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Nanotechnology has emerged as a novel research area to address the several problems associated with existing cancer treatments. Objectives The present work was focused on synthesizing and characterizing the tin oxide-sodium alginate-chlorogenic acid hybrid nanomaterials (SnO2-SA-CA HNMs) for enhanced anticancer effects against breast cancer MDA-MB-231 cells. Materials and Methods The synthesized SnO2-SA-CA HNMs were characterized using several methods, including UV-vis spectroscopy, X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Energy Dispersive X-ray (EDX), Fourier Transform Infrared (FT-IR), Dynamic Light Scattering (DLS) and Photoluminescence (PL) analyses. The MTT assay was done to assess the cytotoxicity of SnO2-SA-CA HNMs against MDA-MB-231 cells. The apoptotic cell death was analyzed by the dual staining assay. The oxidative stress parameter levels were analyzed using corresponding assay kits. Results The results of the different characterization studies are confirmed the formation of metallic SnO2-SA-CA HNMs with an average size of 93 nm. The SnO2-SA-CA HNMs have a crystalline nature, clustered morphology and cuboidal structures. The existence of various functional groups and elements in the HNMs was also confirmed by the FT-IR and DLS analyses, respectively. The SnO2-SA-CA HNMs have demonstrated a substantial effect on inhibiting the viability of MDA-MB-231 cells. The dual staining result also proved the onset of apoptotic cell death in the HNMs-treated cells. The HNMs treatment effectively decreased the antioxidant level, thereby promoting oxidative stress. Conclusion The present findings suggest that SnO2-SA-CA HNMs exhibit potential as a potential therapeutic candidate to treat breast cancer.
Keywords: Breast cancer; Nanomaterials; Apoptosis; Oxidative stress; Chlorogenic acid.